2009
DOI: 10.1104/pp.109.138701
|View full text |Cite
|
Sign up to set email alerts
|

Ripening-Regulated Susceptibility of Tomato Fruit toBotrytis cinereaRequiresNORBut NotRINor Ethylene    

Abstract: Fruit ripening is a developmental process that is associated with increased susceptibility to the necrotrophic pathogen Botrytis cinerea. Histochemical observations demonstrate that unripe tomato (Solanum lycopersicum) fruit activate pathogen defense responses, but these responses are attenuated in ripe fruit infected by B. cinerea. Tomato fruit ripening is regulated independently and cooperatively by ethylene and transcription factors, including NON-RIPENING (NOR) and RIPENING-INHIBITOR (RIN). Mutations in NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(182 citation statements)
references
References 98 publications
8
168
1
5
Order By: Relevance
“…The expression of AP2a appeared to be reduced in all four mutants. Our results suggest that, although AP2a appears at first sight to be a negative regulator of ripening through inhibition of ethylene production, it is itself positively regulated by essential regulators of ripening, like CNR, RIN, and NOR (Barry et al, 2005;Giovannoni, 2007;Cantu et al, 2009), and its expression is ethylene dependent, as shown by its downregulation in the Gr mutant. Next, to test whether the CNR protein could bind directly to the AP2a promoter, we expressed the full-length CNR protein tagged with glutathione S-transferase (GST) (GST-CNR) in Escherichia coli ( Figure 5B.…”
Section: Regulatory Interactions Between Ap2a and Other Ripening Regumentioning
confidence: 87%
“…The expression of AP2a appeared to be reduced in all four mutants. Our results suggest that, although AP2a appears at first sight to be a negative regulator of ripening through inhibition of ethylene production, it is itself positively regulated by essential regulators of ripening, like CNR, RIN, and NOR (Barry et al, 2005;Giovannoni, 2007;Cantu et al, 2009), and its expression is ethylene dependent, as shown by its downregulation in the Gr mutant. Next, to test whether the CNR protein could bind directly to the AP2a promoter, we expressed the full-length CNR protein tagged with glutathione S-transferase (GST) (GST-CNR) in Escherichia coli ( Figure 5B.…”
Section: Regulatory Interactions Between Ap2a and Other Ripening Regumentioning
confidence: 87%
“…The rin (0.04 mg/100 g) and nor (0.15 mg/100 g) mutants recorded low lycopene content, but alc (0.73 mg/100 g) displayed a significantly higher level similar to those of Indian cultivars, and Kopeliovitch et al (1980) have reported a lycopene content in alc of 1.182 mg/100 g. The low lycopene contents of the nor and rin ripening mutants agree with the results of others Tigchelaar et al, 1976). In both nor and rin mutants, the fruits develop normally before the mature green stage, but once mature, they fail to synthesize lycopene and other carotenoids (Cantu et al, 2009). However, the F 1 (alc x 'Pusaruby') showed significantly higher values (1.75 mg/100 g), whereas the values for other hybrids were similar to those of the Indian cultivars.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…Shelf life of tomato is determined by two processes: the rate of fruit softening during overripening (which is the stage that follows commercial maturity, when the fruit softens and loses its organoleptic properties, including its characteristic taste and flavor), and susceptibility to opportunistic pathogens such as Botrytis cinerea (Cantu et al, 2009). B. cinerea, better known as gray mold, is the second most important fungal pathogen of plants, economically (Dean et al, 2012).…”
mentioning
confidence: 99%